The Effect of the Family Hope Program on Poverty Reduction in Sinarjaya Village, Pandeglang Regency in 2025 - Nurdin, Ali; Nurrahma, Tita Aurellya (MID Publisher International, 2024)
This study analyzes the impact of the Family Hope Program (PKH) on poverty reduction in Sinarjaya Village, Pandeglang Regency. PKH is a conditional cash transfer designed to assist very poor families by improving access to education, health, and social welfare. Using a mixed-method approach with an explanatory sequential design, the research combines quantitative and qualitative analyses. The study involved 325 PKH beneficiary families, with 120 respondents selected through stratified random sampling. Data were collected through surveys, in-depth interviews, observations, and document reviews, and analyzed using multiple regression and path analysis. The findings reveal that PKH significantly contributes to reducing both economic and multidimensional poverty levels. Improved access to education and health services mediates the positive effects of the program. However, its effectiveness is influenced by local institutional capacity, targeting accuracy, and the beneficiaries’ consumption patterns, which remain mostly consumptive. The study recommends strengthening community assistance, improving data accuracy, and integrating PKH with local economic empowerment initiatives to ensure sustainable poverty alleviation.